Development of Epileptic Seizure Symptoms Detection Device - Zamry, Siti Aishah; Yahya, Roshayati (Journal of Electronic Voltage and Application, 2025)
This paper shows a seizure detection device developed with a pulse oximeter, accelerometer, and vibration sensor. A 9V battery, LM2596 voltage regulator, and two ESP32 microcontrollers were also used in the development process. The pulse oximeter is a sensor whose purpose is to measure the patient's activity level: oxygen saturation, and heart rate. The accelerometer detects motion or activity in a patient's body, which could indicate a possible seizure. On the other hand, a jerky body movement manifested during seizure is detected by the vibration sensor to help in increasing the efficiency of the seizure detection model. The ESP32 microcontroller was interfaced with the sensors in the proposed device to enable data collection and transmission. The LM2596 voltage regulator was added to ensure that power from a 9V battery is always on. The Blynk app provides notifications or alerts to the caregivers whenever there is a seizure. To epileptic patients, this device assures their safety and quality of life because of providing a fast intervention and on-time monitoring. Complete seizure detection is achieved by integrating different kinds of sensors and microcontrollers, while the Blynk app is there to ensure its proper communication with the caregivers for effective and efficient management of the care.